HUBUNGAN ANTARA DUKUNGAN SOSIAL KELUARGA DAN MOTIVASI DENGAN KEPATUHAN BEROBAT PASIEN DIABETES MELLITUS (DM) TIPE II DI WILAYAH KERJA PUSKESMAS X GRESIK - Qulbi Ainin Nuha; Windah Riskasari; Puri Aquarisnawati (Fakultas Psikologi Universitas Hang Tuah, 2023)
This study aims to determine the relationship between family social support and motivation with adherence to treatment of type II diabetes mellitus (DM) patients in the work area of PUSKESMAS X Gresik. This study used a quantitative approach survey method with the study subjects totaling 72 type II diabetes mellitus (DM) patients. The sampling technique uses accidental sampling. Analysis of data used for product moment and multiple correlation with the help of SPSS version 25. The research scale consisted of a treatment compliance scale of 14 sahih aitems (α=0.889), a family social support scale of 16 sahih aitems (α=0.931), and a motivation scale of 12 sahih aitems (α=0.859). The major hypothesis obtained a correlation coefficient value of 0.927 which means it is greater than the table R at N=72 with a significant level of 5% which is 0.192 (0.927 is more than 0.192) then there is a significant positive relationship between family social support and motivation with adherence to treatment, the effective contribution value of 27.2%. The first minor hypothesis was accepted with a correlation coefficient value of 0.243 and a significant level of 0.040 is less than 0.05, which means that there is a significant positive relationship between family social support and adherence to treatment. The second minor hypothesis is accepted with a correlation coefficient value of 0.428 and a significant level of 0.000 is less than 0.05, which means that there is a significant positive relationship between motivation and adherence to treatment.